Standardized short‐term acute heat stress assays resolve historical differences in coral thermotolerance across microhabitat reef sites. (21st June 2020) - Voolstra, Christian R.; Buitrago‐López, Carol; Perna, Gabriela; Cárdenas, Anny; Hume, Benjamin C. C.; Rädecker, Nils; Barshis, Daniel J.
Abstract: Coral bleaching is one of the main drivers of reef degradation. Most corals bleach and suffer mortality at just 1–2°C above their maximum monthly mean temperatures, but some species and genotypes resist or recover better than others. Here, we conducted a series of 18‐hr short‐term acute heat stress assays side‐by‐side with a 21‐day long‐term heat stress experiment to assess the ability of both approaches to resolve coral thermotolerance differences reflective of in situ reef temperature thresholds. Using a suite of physiological parameters (photosynthetic efficiency, coral whitening, chlorophyll a, host protein, algal symbiont counts, and algal type association), we assessed bleaching susceptibility of Stylophora pistillata colonies from the windward/exposed and leeward/protected sites of a nearshore coral reef in the central Red Sea, which had previously shown differential mortality during a natural bleaching event. Photosynthetic efficiency was most indicative of the expected higher thermal tolerance in corals from the protected reef site, denoted by an increased retention of dark‐adapted maximum quantum yields at higher temperatures. These differences were resolved using both experimental setups, as corroborated by a positive linear relationship, not observed for the other parameters. Notably, short‐term acute heat stress assays resolved per‐colony (genotype) differences that may have been masked by acclimation effects in the long‐term experiment. Using our newly developed portable experimental system termed the Coral Bleaching Automated Stress System (CBASS), we thus highlight the potential of mobile, standardized short‐term acute heat stress assays to resolve fine‐scale differences in coral thermotolerance. Accordingly, such a system may be suitable for large‐scale determination and complement existing approaches to identify resilient genotypes/reefs for downstream experimental examination and prioritization of reef sites for conservation/restoration. Development of such a framework is consistent with the recommendations of the National Academy of Sciences and the Reef Restoration and Adaptation Program committees for new intervention and restoration strategies. Abstract : Coral bleaching drives reef degradation, but some species and genotypes resist or recover better than others. We conducted a series of 18‐hr short‐term acute heat stress assays side‐by‐side with a 21‐day long‐term heat stress experiment to show that thermotolerance differences between reef sites were resolved using both experimental setups. Importantly, only short‐term acute heat stress assays resolved per‐colony (genotype) differences. Using our newly developed Coral Bleaching Automated Stress System (CBASS), we thus highlight the potential of mobile, standardized short‐term acute heat stress assays to resolve fine‐scale differences in coral thermotolerance.